Modelagem espaço-temporal das arboviroses nas regiões de saúde do estado da Bahia: uma abordagem epidemiológica e ambiental - Souza, Jessica Suzarte Carvalho de (2022)
Currently, arboviruses (Dengue, Zika and Chikungunya) have become a public health problem, due to the progressive and uncontrolled increase in cases. At the same time, in mid-March 2020, Bahia was faced with a serious and often lethal disease, which became the center of attention in different regions of the world, the covid-19, generating another public health problem, reducing the concern regarding the prevention and control of arboviruses. Analyzing the current situation of diseases transmitted by arboviruses in Brazil, Bahia was taken into account, since in recent years arboviruses have been growing progressively in this state. In view of this scenario, this dissertation aims to analyze the temporal trend of arbovirus rates registered in the health regions of the State of Bahia, using statistical and computational methods as a foundation. The quantitative data came from the Bahia State Health Department (SESAB), made available by the Information Technology Department of the Unified Health System (DATASUS). Population data by the Brazilian Institute of Geography and Statistics (IBGE). Statistical analyzes comprised univariate analysis (position measures, measures of dispersion and asymmetry) and bivariate analysis (Pearson's correlation coefficient and simple linear regression model with Prais Winsten correlation) and the Granger causality test. We identified positive and negative linear correlations between the rates of arbovirus notifications with the time series of relative air humidity and air temperature, from January 2017 to December 2019, in the municipality where the health region of Feira de Santana is located. -BA. The health region of Barreiras had the highest average rate of dengue cases per 100.000 inhab, Irecê in the Chikungunya rates and Vitória da Conquista in the Zika rates in the period from March 2020 to June 2021. The highest monthly percentage changes (MPV) and statistically significant, with 95% confidence, in relation to the rates of reported cases of dengue was the region of Santo Antônio de Jesus and Teixeira de Freitas in the rates of cases of Chikungunya and Zika. The findings obtained in this research may support other studies related to this theme, in addition to contributing as an indicator for evaluations of the planning of public health policies, maintenance and integration of epidemiological surveillance, which prioritize popular participation and health professionals in detection, prevention and control of arboviruses.